Bridging finance and sustainability: A systematic review of responsible investment (RI) performance in BRICS markets - Anna Kovalchuk (Sustainable Futures, 2025)
Compounding integration of responsible investment (RI) principles with financial innovation creates significant opportunities to address sustainability challenges during periods of economic uncertainty, crises, and energy transitions. Before developing effective RI solutions, it is crucial to clearly understand how RI frameworks operate and the key dimensions around which they are structured. The purpose of this study is to critically analyze and evaluate existing research on RI in emerging markets, establishing a systematic basis for assessing its performance in sustainable development contexts. This investigation employs a dual-method approach, combining systematic literature review with bibliometric analysis elements, to: (1) conceptualize RI parameters in emerging market contexts, (2) establish performance benchmarks for crisis-period energy transitions, and (3) develop criteria for sustainability indicator selection. The results elucidate RI’s bifunctional capacity as both a stabilizing force during economic disruptions and an accelerator of sustainable capital deployment. The study yields three substantive contributions: a robust framework for RI performance evaluation, actionable protocols for investment decision-making, and targeted policy instruments enabling BRICS economies to operationalize SDG-7 (Clean Energy) and SDG-9 (Industry Innovation) via RI-aligned financing mechanisms. Supporting bibliometric analysis reveals accelerating interdisciplinary synthesis between financial and sustainability research domains, with emerging markets demonstrating particularly dynamic scholarly engagement.